THE ANALYSIS OF PROVIDING INCENTIVES ON ISLAMIC HOLIDAYS IN MICRO, SMALL AND MEDIUM ENTERPRISES: DO EXTRA-ROLE BEHAVIOR MATTER? - Sefia Alika Indriani; Frida Fanani Rohma; Abdul Halim (Accounting Journal of Ibrahimy (AJI), 2024)
Incentives are considered one of the main factors to encourage individual work motivation. Providing both the monetary amount and the timing of incentives is within the full authority of the business owner without any binding or fixed-time obligations. This research uses a qualitative method involving Micro, Small and Medium Enterprises (MSMEs) that produce garments as the research site. The findings of this research indicate that incentives specifically given on Islamic holidays have a crucial impact on increasing the activation of work motivation, which impacts overall organizational performance to encourage the creation of goal alignment. Providing incentives to Islamic majors is more than just encouraging performance because the monetary incentives given on Islamic holidays are not only interpreted as monetary incentives for rational economic people. Moreover, giving during Islamic holidays is seen as a manifestation of tolerance, which has a more crucial impact on efforts to optimize extra-role behaviour, thereby encouraging increased performance.